PENGARUH MANUVER KENDARAAN PARKIR PADA BADAN JALAN TERHADAP KARAKTERISTIK LALU LINTAS DAN BIAYA OPERASIONAL KENDARAAN (STUDI KASUS PADA JALAN BRIGADIR POLISI ABDUL KADIR) KOTA PALEMBANG - A Fuad Z; Revias Noerdin (Politeknik Negeri Sriwijaya, 2014)
By having the parking activity on both sides of road, right and left which use a part of road,it causes the decrease of road capacity and road service level on Jalan Abdul Kadir. It also influences the volume, the speed and the density on the street.The purpose of the research is to find out parking activity influence level on both road sides, right and left, to know the influence of vehicles’ maneuver while entering and leaving on street parking toward traffic characteristic, to find out the delayed time caused by of street parking vehicles’ maneuver, to know financial loss because of delay relating to vehicles operational cost, to find out the alternative solution of road performance which caused by on street parking activity.From the analysist result, it was obtained that the road capacity was equal to 3,251.03 emp/h. The peak hour factor (PHF) or road service was 0.61. It was less than 0.7. The traffic capacity after on street parking was 3,129.7 emp/h with 0.64 PHF. It was less than 0.7. It means there was capacity reduction. The road capacity can be seen on maximum traffic volume or on peak hours on Monday at 09.00 till 10.00. It was 1,907 emp/h, the average speed (S) was 40.51km/h, and the density or D was 47.06 emp/km. The average delay was 5.61second/hour. The vehicles operational cost before delayed time calculating was Rp. 2,004.44/km. Meanwhile, after delayed time calculating was Rp.2.504.4/km. It can be concluded that there was financial loss about Rp 500.00/h each vehicle. Based on service level this street has not yet needed physical repair. It is adequate with the street management. Moreover, from the analysist which shows that the number of opposite parking vehicles maneuver was 199 of 493 vehicles which are going to be parked. It was about 40.36 % with delayed time about 6.75 second. From the above explanation, the writer suggets that the street become one way. By becoming one way street, there will be no opposite parking vehicles maneuver.